The Labour Market in Winter : the State of Working Britain. - Gregg, Paul (OUP Oxford, 2011)
This collection of essays, from leading economic experts on the UK labour market, provides an overview of the key issues concerning the performance of the labour market, and the policy issues surrounding it, with a focus on the recent recession and its aftermath. The book contains assessments of the effects of many policies introduced over the last 10 years in employment, education, and welfare. The result is the first serious comprehensive analysis of the economic downturn and the Labour government's record in the field of employment, spanning its time in office. An indispensable reference so.